PENGARUH KUALITAS PELAYANAN KESEHATAN, BRAND IMAGE DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS BABADAN KABUPATEN PONOROGO - Retno, Retno Ambarwati; Haryanto, Aris Tri; Suryo Sardjono, Herning (JI@P, 2024)
The purpose of this research is to know the effect of health service quality, brand image and trust on patient satisfaction. This research is survey research and is classified as explanatory research. This research was conducted at the Babadan Community Health Centre, Ponorogo Regency. The research population was Babadan Health Centre patients with a sample of 100 people used accidental sampling technique. Data collection techniques used questionnaires, observation and literature study. The data analysis technique used multiple linear regression. The results of the research show that the quality of health services has a significant effect on patient satisfaction, where the better the quality of health services can increase patient satisfaction. Brand image has a significant effect on patient satisfaction, where the better the brand image can increase patient satisfaction. Trust has a significant effect on patient satisfaction, where better trust can increase patient satisfaction.